Health Behavioral Patterns Associated with Psychologic Distress Among Middle-Aged Korean Women - Hye-Sook Shin, PhD, RN; Jia Lee, PhD, RN; Kyung-Hee Lee, PhD, RN; Young-A Song, PhD, RN (Elsevier, 2007)
Middle aged women are exposed to high levels of psychologic distress due to various factors including health problems of family members, their own declining health, negative outlook towards menopause, loss of significant supportive relationships, and uncertainties regarding the future. The purpose of this study was to identify the factors associated with psychologic distress of middle-aged Korean women in the Seoul metropolitan area. Methods: The data were collected from 277 community-dwelling women between the ages of 40 and 60 years without any known severe illnesses from May 6, 2004 to May 31, 2004. The researcher or two research assistants visited the participants in person, handed out copies of the questionnaire after receiving study permission, and answered if they had any questions. Results: Hierarchical multiple regression analysis found that women with low scores of health promoting behaviors for self-actualization, nutrition, and interpersonal relation reported high levels of psychologic distress. In addition, women with low scores of marital satisfaction reported high psychologic distress. Conclusion: The study found cultural characteristics of middle-aged Korean women in psychologic distress. Health care providers should consider marital satisfaction, self-actualization, nutrition, and interpersonal relations, in particular, among Korean middle-aged women.